2017
DOI: 10.4236/opj.2017.711021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Optical Properties for Square, Circular and Hexagonal Photonic Crystal Fiber

Abstract: This paper presents four rings square, circular, and hexagonal photonic crystal fiber (PCF) geometry for analyzing different optical properties in a wavelength ranging from 800 nm to 1600 nm. These three types of geometry have been used for analyzing Effective area, Propagation constant, Confinement loss and Waveguide dispersion. Silica glass is chosen as background material and the cladding region is made of four air hole layers. COMSOL Multiphysics (v.5) software is used to simulate these proposed PCF geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…where Re(n eff ) and Im(n eff ) are the real and imaginary parts of β. The confinement loss (CL) can be calculated as [30][31][32]…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…where Re(n eff ) and Im(n eff ) are the real and imaginary parts of β. The confinement loss (CL) can be calculated as [30][31][32]…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…Because of its ability to control light in hollow bodies, the loss of blockage is very low and the contact of light is increased, resulting in increased fiber sensitivity [2]. A number of reported works [3][4][5][6][7][8][9][10][11][12][13][14][15][16] have been developed to investigate the performance of optical sensors based on PCF. In several applications, PCF is used, such as gas detection [3][4], chemical detection [5][6], pressure detection [7], biomedical and temperature sensing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These bio-sensing and chemical senses play an important role in medical science. As a result, most researchers keep an eye on the detection of fluid, chemical, and gas sensitivities [12][13][14][15][16]. Several numbers of research studies on gas detection were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Where in conventional fibers, designing is not so easy, core size is limited, material selec- tion is tough etc. Moreover, these limitations on the geometry hamper the flexibility in recognizing fiber properties such as dispersion [2] [7], confinement loss [8] [9], birefringence [2] [9], relative sensitivity [10] etc. PCF provides us with long distance light propagation that was not possible previously.…”
Section: Introductionmentioning
confidence: 99%
“…Light propagation characteristics can be controlled by adjusting the air holes in the core and cladding region. A lot of research studies are already done in the fields of optical communications [10] [11], nonlinear optics [11] and sensing [12] [13] [14].…”
Section: Introductionmentioning
confidence: 99%